Panowanie króla Jerzego ze śląskiej perspektywy (w 550. rocznicę śmierci monarchy) - Czechowicz, Bogusław (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
This review article presents the reign of George of Poděbrady, King of Bohemia, from a Silesian perspective, therefore contrary to dominant Bohemocentric option. The author also opposes the historiographic myths created by the Czech researchers, in which George of Poděbrady is nearly adored, without any deeper attempts of critical assessment of his reign.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne